Patterns of bias in Hollywood movies - Cones, John W. (Algora Pub., 2012)
This work grew out of the observed frustration of film industry critics who have pointed out examples of bias and stereotyping in specific Hollywood movies over the years only to be rebuffed by the simplistic studio arguments that such films reflect the real world and that moviegoers vote with their pocket books. It can be shown that there is a consistent pattern to the choices Hollywood studio executives make with respect to the movies produced and released and the specific content of those movies, and it becomes obvious that Hollywood is selectively portraying reality. Movie goers only have.